THE SOCIAL CONSTRUCTION OF TIWALA IN A RURAL POOR COMMUNITY - Mangubat, Lilly V. (Philippine Journal of Social Development; 2008, 2010)
Among the research participants in a farming community, tiwala (roughly, trust) appears to be a mechanism that provides some semblance of stability and predictability in a precarious world. It provides a symbol of dependability and is associated with social support systems which help people cope with the difficulties of daily living. Further, the data suggest that people’s organizations become symbols of tiwala when the marginalized interpret them as embodying not only their ideals but also addressing the immediate and concrete concerns in their daily lives.